The Expressions of Co‐Stimulatory Molecules are Altered on Putative Antigen‐Presenting Cells in Cord Blood. (16th October 2012) - Darmochwal‐Kolarz, Dorota; Serafin, Andrzej; Tabarkiewicz, Jacek; Kolarz, Bogdan; Rolinski, Jacek; Oleszczuk, Jan
<x xml:space="preserve">Abstract</x> Problem The aim of our study was to estimate the expressions of both B7‐H1 and B7‐H4 as well as CD200 and CD200R co‐stimulatory molecules on immature myeloid and lymphoid dendritic cells, B CD19+ lymphocytes and monocytes in umbilical cord blood of healthy neonates and in peripheral blood of healthy adults. Method of study Thirty‐nine healthy full‐term neonates from physiological single pregnancies and 27 healthy adults were included in the study. The expressions of B7‐H1, B7‐H4, CD200, CD200R antigens were estimated using flow cytometry. Statistical analysis was performed using a non‐parametric Mann–Whitney U‐test and parametric Wilcoxon's test. Results The expressions of B7‐H1 and B7‐H4 molecules on immature BDCA‐1+ myeloid dendritic cells were significantly lower in umbilical cord blood of healthy neonates when compared with those cells in peripheral blood of healthy adults (P < 0.0001). Furthermore, the suppression of B7‐H4 molecule on BDCA‐2+ lymphoid dendritic cells was observed in cord blood of healthy neonates when compared with peripheral blood of healthy adults (P < 0.02). The expressions of CD200 antigen on BDCA‐1+ cells, CD200R antigen on BDCA‐2+ cells and CD200R antigen on B CD19+ cells were significantly lower in cord blood of healthy neonates. On the other hand, the expressions of CD200 and CD200R as well as B7‐H4 co‐stimulatory molecules on CD14+ cells were significantly higher in cord blood when compared with peripheral blood. Conclusion The increased percentages of CD14+ monocytes with the expressions of CD200 and CD200R as well as B7‐H4 co‐stimulatory molecules can suggest the increased immunomodulatory properties of neonatal monocytes in cord blood.